Sintesis Dialdehid Alginat Melalui Reaksi Oksidasi Natrium Alginat Dengan Natrium Metaperiodat - Subur P Pasaribu; Jamaran Kaban; Mimpin Ginting; Kasmirul Ramlan Sinaga (JURNAL KIMIA MULAWARMAN, 2017)
Synthesis of dialdehyde alginate has been done by oxidation reactions of sodium alginate with sodium metaperiodate (ratio of mol 1: 1). The formation of dialdehyde alginate as a result of oxidation are characterized by FT-IR spectroscopy with a peak absorption at 1627.92 cm-1, which is the vibration stretching C = O of functional groups from the aldehyde group resulting from the -OH group oxidation process, the absorption peak is changing its wavelength and intensity more sharply compared to initial sodium alginates. In addition, the C-O-C band (cyclic ether ) at 1033 cm-1 are reduced as a result of chains cleavage. The absorption peaks that appear at 794.67 cm-1 and 732.95 cm-1 are included in the bond CH which contributes to cleavage the bending C-C of oxidized sodium alginate.